Junkyard dreams a novel - Boyer, Jeanette (Albuquerque : University of New Mexico Press, 2007)
Rita Vargas owns an automobile junkyard outside of Santa Fe. Her property abuts a hill with a spectacular view, making the junkyard a magnet for ubiquitous developers. But Rita's land has been in her family for generations, and she doesn't want to sell. Also, her son Parker, a talented artist, uses salvaged pieces from the junkyard for his sculptures. Local wheeler-dealer Leroy Sena has already bought the ridge above Rita's property, and when Leroy sells that land to a small-time landlord and his gallery-owner sweetheart, the stakes are raised.
89413
Keywords: Automobile graveyards -- New Mexico -- Santa Fe -- Fiction; Single women -- Fiction; Real estate developers -- Fiction; Santa Fe (N.M.) -- Fiction